Safety of Interhospital ECMO Transport by Low-Volume ECMO Transport Centers - Singh, Kalpana; Ojito, Jorge; Sasaki, Jun (Journal of Pediatric Intensive Care, 2020)
We present our 20 years of experience as a low-volume extracorporeal membrane oxygenation (ECMO) transport center from the Southeast United States. This is a retrospective chart review of all ECMO transported patients between 1998 and 2017. Of 26 patients who were ECMO transported, median age was 15.5 days, 14 patients (54%) were neonates, 18 (69%) patients had primary cardiac pathologies, and 16 (61.5%) patients had primary ECMO transport. Median distance traveled was 81 miles. All patients were on venoarterial ECMO. Complications occurred in three patients (11.5%). Survival to discharge was 69%. Neonatal and pediatric ECMO transport by a low-volume ECMO transport center is safe.
Keywords: extracorporeal membrane oxygenation; transport; pediatrics; neonatal